2021
DOI: 10.1111/jac.12549
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chilling at the booting and flowering stages on rice phenology and yield: A case study in Northeast China

Abstract: Climate change has resulted in a continuous increase in the frequency and intensity of chilling events in cold regions. In Northeast China, chilling at the booting and flowering stages negatively affects japonica rice grain yield. In this field experiment study, we conducted a 2‐year temperature‐controlled experiment to investigate the effects of chilling temperature and duration applied at the booting and flowering stages on japonica rice. The results showed that chilling at the two study stages delayed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Our previous results with this same experiment showed that LTS after flowering did not significantly decrease grain weight, except under D3T4 treatment in Nanjing 46 ( Ali et al, 2021 ). And this result was similar to the previous studies ( Huang et al, 2021 ; Shi et al, 2021 ). Therefore, we assume that the main reason for the dilution effect of the amino acids content could be the decreasing grain number due to reduced seed-setting rate under LTS, as reported in our previous study ( Ali et al, 2021 ), and the decreasing grain number under LTS could significantly reduce the sink capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our previous results with this same experiment showed that LTS after flowering did not significantly decrease grain weight, except under D3T4 treatment in Nanjing 46 ( Ali et al, 2021 ). And this result was similar to the previous studies ( Huang et al, 2021 ; Shi et al, 2021 ). Therefore, we assume that the main reason for the dilution effect of the amino acids content could be the decreasing grain number due to reduced seed-setting rate under LTS, as reported in our previous study ( Ali et al, 2021 ), and the decreasing grain number under LTS could significantly reduce the sink capacity.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the frequency and severity of extreme temperature events are increasing even under global warming due to phenological shifting, and the frequency of LTS is higher at the flowering and grain filling stages of late rice and single rice. In recent years, most studies have focused on the impact of climate changes on rice grain yield ( Shi et al, 2021 ), the majority of which are related to high-temperature stress and drought ( Chen et al, 2017 ; Zhen et al, 2020 ). A few studies have focused on the impact of LTS on rice quality based on protein and starch content ( Zeng et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once the rice plants in the pots reached the targeted tillering (25 days after transplanting), booting (the upmost pulvinus interval of main stems are −5~−7 cm) and flowering (the main stems bloom up to 10%) stages, they were transferred into naturally lit growth chambers (4 m long, 4 m wide and 3.5 m high) for artificial chilling treatment (Figure 1a). Based on previous research (Guo et al, 2022; Shi, Guo, Wang, et al, 2022) and historical meteorological data (Figure S1), we selected the average temperature of 12°C (extreme chilling temperature level) and 18°C (chilling temperature level that may be encountered in actual production) as the treatment temperature and the intermittent days were set to 2 days, the diurnal temperature was 10°C (Figure S2). There were four chilling durations of D2, D4, D6 and D8 for the continuous and intermittent chilling treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Rice plants are generally more sensitive to chilling during reproductive than vegetative stages in crop development (Jacobs & Pearson, 1999; Korres et al, 2017; Sanchez et al, 2014). Chilling reduces the tiller, and hence decreases the grain number per spike, spikelet fertility and grain weight, which collectively jeopardizes the rice grain yield formation (Shi, Guo, Wang, et al, 2022; Zhu et al, 2017). At the tillering stage, chilling reduces the rate of tillering, leaf appearance and leaf elongation (Tanaka, 1962).…”
Section: Introductionmentioning
confidence: 99%
“…Chilling at the flowering stage could damage anther dehiscence, pollination, and pollen germination, as well as decrease spikelet fertility (Yoshida, 1981). Usually, the main stems and tillers are already separated at the flowering stage, and the chilling stress mostly affects spikelet fertility but barely affects the number of grains per panicle (Shi et al, 2021).…”
Section: Main Yield Components Affecting the Rice Grain Yield With Ch...mentioning
confidence: 99%